Critical success factors for Vietnamese laboratories striving to implement quality management systems - Cathy Robinson; James Johnson; Katy Yao; Hien Bui (AOSIS, 2020)
Accurate laboratory reporting is crucial to patient diagnosis and treatment. This study identified critical success factors (CSF) for implementing a laboratory quality management system (QMS). This descriptive research used qualitative and quantitative methods to collect and analyze data from laboratory managers and staff employed in Vietnamese hospital laboratories implementing a QMS. The top five CSFs identified were: (1) staff QMS knowledge, (2) manager leadership, (3) staff commitment, (4) mentorship, and (5) hospital administration support. Identifying CSFs is critical to successful planning and implementation of QMS.